Exploration of the regulation of immunomodulatory genes by commelina benghalensis aqueous extra in breast cancer cells - Mnisi, Hellen Laura (My University, 2025)
Cancer is a noteworthy global health issue, and according to predictions by the World Health Organization, the number of new cases was projected to increase to approximately 29-37 million by 2040, worldwide (WHO, 2020, Sung et al., 2021). Female breast cancer has been shown to be the leading cause of global cancer incidence in 2020, with reported 2.3 million new cases, representing 11.7% of all cancer cases (Reyes-Monasterio et al., 2022). Treatments such as surgery, radiotherapy, and chemotherapy are used to counteract breast cancer; however, these treatment approaches are now ineffective, which has led to the shift of interest towards the use of medicinal plants such as Commelina benghalensis (Cb), which has been traditionally used in folk medicine to treat various ailments, including inflammation-related conditions. Studies reveal that the plant contains bioactive compounds, such as flavonoids, tannins and phenolics, which possess anti-inflammatory, antioxidant, and antitumor properties (Islam et al., 2018; Islam et al., 2017; Islam et al., 2016). Thus, the aim of the study was to determine the antioxidant and anticancer properties of Cb aqueous extract in breast cancer cells. Breast cancer cell lines, MDA-MB 231 and MCF-7, were cultured and maintained in appropriate growth media. The Cb was extracted using only water, and this was done to mimic what the traditional healers do, when they prepare medicinal plants concoctions for medicinal purposes. The profiling of the bioactive compounds was done using Thin Layer Chromatography (TLC), phytochemical screening, and the Liquid Chromatography-Mass Spectrometry (LC-MS). The total amount of phenols, flavonoids and tannin in the Cb aq-extract was quantified using the Folin-Ciocalteu Colorimetric Assay. Additionally, the antioxidant activity was done using 2, 2-Diphenyl-1-picrylhydrazyl (DPPH) and free radical antioxidant power (FRAP) assays. Furthermore, the cytotoxicity effect of Cb aqueous extract was determined against the breast cancer using 3-(4, 5-dimethylthiazolyl-2)-2, 5-diphenyltetrazolium bromide (MTT) assay. The Muse® Cell Count and Viability assay was done to confirm the MTT results. Morphological changes were observed using light microscopy and the images were captured using computer connected to microscope. Moreover, Annexin V assay was conducted to investigate the potential cell death that may be induced by the Cb leaf-aq extract. The TLC plates demonstrated that the Cb root, leaf and stem-aq extract have bioactive molecules. The quantitative phytochemical analysis using Folin-Ciocalteu Colorimetric Assays, showed that the Cb aq extracts had high phenolic, flavonoid and low tannin contents Folin-Ciocalteu Colorimetric Assays. Moreover, the Cb aq-extracts demonstrated antioxidant properties, and this was mostly observed in the leaf and the root parts of the plant. The LC-MS results of Cb leaf-aq extract demonstrated the presence of bioactive compounds that have been previously shown to exhibit anticancer cancer immunomodulatory activities. In this study, three compounds with immunomodulatory effects; namely, Abietic acid, Vorinostat and Lauramide, were identified. These compounds regulate a number of cytokine genes, and these include TGF-b1, IGF1R, IFN, IL-2, IL-4, IL-10, IL-13. Additionally, the Cb leaf-aq significantly (**P ˂ 0.01, ***P ˂0.001 and ****P ˂0.0001) reduced the viability of MDA-MB 231 cells after 24- and 48-hours treatment with 500 and 1000μg/ml compared to other parts of the plant. Furthermore, the Cb leaf aqueous extract significantly (****P ˂0.0001) induced apoptosis of MDA-MB-231 cells after their treatment with the IC50 concentration (750μg/mL). These findings collectively support the conclusion that the phytocompounds identified in Cb have anticancer properties and a potential to modulate immunological responses in breast cancer cells.
Thesis (M.Sc. (Biochemistry)) -- University of Limpopo, 2025
Keywords: Breast cancer; Cancer; Cells; Cancer cell; Breast -- Cancer; Cancer cells -- Growth